STRATEGY TO IMPROVE INSTRUCTOR PERFORMANCE THROUGH IMPROVING PERCEIVED ORGANIZATIONAL SUPPORT, SERVANT LEADERSHIP, TEAMWORK, EMPLOYEE ENGAGEMENT AND WORK MOTIVATION OF BBPLK INSTRUCTORS IN WEST JAVA PROVINCE - Tanti Susilarini; Rita Retnowati; Dian Wulandari (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
The performance of instructors at the Vocational Training and Productivity Center (BBPLK) in West Java faces several challenges, including limited perceived organizational support, incomplete servant leadership practices, weak teamwork, and low employee engagement and work motivation. This study aims to analyze strategies to improve instructor performance by strengthening perceived organizational support, servant leadership, teamwork, employee engagement, and work motivation. A quantitative survey method was employed using Path Analysis and SITOREM analysis. The sample consisted of 133 instructors selected proportionally from a population of 198 instructors at BBPLK Bandung and Bekasi. The results show that all independent variables have a significant positive direct effect on performance, with perceived organizational support as the strongest predictor (beta = 0.303). Perceived organizational support, servant leadership, and teamwork also significantly influence employee engagement and work motivation. Employee engagement and work motivation function as mediating variables, although their contribution is relatively small. SITOREM analysis identifies priority areas for improvement, including efficiency, fairness, member development commitment, team synergy, vigor, and recognition. The findings suggest that improving instructor performance requires an integrated approach combining organizational support, servant leadership, teamwork, engagement, and motivation.